2017
DOI: 10.3171/2017.5.focus17196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of spinal endoscopic discectomy–assisted oblique lumbar interbody fusion: preliminary results

Abstract: OBJECTIVEDirect neural decompression cannot be achieved by performing lateral lumbar interbody fusion (LLIF). To overcome the indirect decompressive effect of LLIF, additional endoscopic discectomy with oblique lumbar interbody fusion (OLIF) has been attempted. The purpose of this study was to assess the clinical and radiological outcomes of patients who underwent OLIF with additional endoscopic discectomy.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
(33 reference statements)
0
38
0
Order By: Relevance
“…8−11 Compared with transforaminal lumbar interbody fusion (TLIF) or posterior lumbar interbody fusion (PLIF), OLIF can maximally preserve posterior structures, including ligamentous structures, muscle and facet joints, however, OLIF does not access to spinal canal and the resulting indirect decompression is a drawback and restricts the application of OLIF, expecially for lumbar degenerative disease accompanied by prolapsed disc herniation or severe lumbar spinal stenosis, which are contraindications of OLIF. 12,13 For the above situations, surgeons always choose traditional TLIF or PLIF for direct decompression. However, the risk of substantial bleeding, direct neural injury, epidural adhesion, and posterior ligamentous injury are disadvantages of TLIF and PLIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8−11 Compared with transforaminal lumbar interbody fusion (TLIF) or posterior lumbar interbody fusion (PLIF), OLIF can maximally preserve posterior structures, including ligamentous structures, muscle and facet joints, however, OLIF does not access to spinal canal and the resulting indirect decompression is a drawback and restricts the application of OLIF, expecially for lumbar degenerative disease accompanied by prolapsed disc herniation or severe lumbar spinal stenosis, which are contraindications of OLIF. 12,13 For the above situations, surgeons always choose traditional TLIF or PLIF for direct decompression. However, the risk of substantial bleeding, direct neural injury, epidural adhesion, and posterior ligamentous injury are disadvantages of TLIF and PLIF.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the indications for OLIF might be extended when it combined with the assistance of spinal endoscopic discectomy, that direct decompression for intervertebral foramen or spinal canal would be realized. 12,13 So far, spinal endoscopic discectomy-assisted OLIF has been rarely reported and there are several limitations in previous studies. 12−14 In present study, we retrospectively analyzed 15 patients who had degenerative lumbar spondylolisthesis, lumbar spine instability or lumbar spinal stenosis accompanied by prolapsed disc herniation, and receieved treatment of OLIF combined with percutaneous transforaminal endoscopic discectomy (PTED).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested using direct decompression in case of spinal stenosis with the concomitant herniated lumbar disc 9) . The additional of endoscopic discectomy could directly decompress neural element without the needs of posterior decompression 6) . Another advantage of endoscopic-assisted OLIF is an ability to directly visualized the quality of end plate preparation with 30 degrees endoscopic lens 6) .…”
Section: Prevalence Of Asdeg After Lumbar Spinal Surgery Is 31-83% 414)mentioning
confidence: 99%
“…The additional of endoscopic discectomy could directly decompress neural element without the needs of posterior decompression 6) . Another advantage of endoscopic-assisted OLIF is an ability to directly visualized the quality of end plate preparation with 30 degrees endoscopic lens 6) . Because OLIF was done in right lateral decubitus position with approach from the left, central and right side pathology may be easier to reach with endoscopic assisted.…”
Section: Prevalence Of Asdeg After Lumbar Spinal Surgery Is 31-83% 414)mentioning
confidence: 99%
See 1 more Smart Citation